Hot-mode accretion and the physics of thin-disc galaxy formation. Issue 4 (14th June 2022) - Hafen, Zachary; Stern, Jonathan; Bullock, James; Gurvich, Alexander B; Yu, Sijie; Faucher-Giguère, Claude-André; Fielding, Drummond B; Anglés-Alcázar, Daniel; Quataert, Eliot; Wetzel, Andrew; Starkenburg, Tjitske; Boylan-Kolchin, Michael; et al.
ABSTRACT: We use FIRE simulations to study disc formation in z ∼ 0, Milky Way-mass galaxies, and conclude that a key ingredient for the formation of thin stellar discs is the ability for accreting gas to develop an aligned angular momentum distribution via internal cancellation prior to joining the galaxy. Among galaxies with a high fraction (70 per cent ) of their young stars in a thin disc ( h / R ∼ 0.1), we find that: (i) hot, virial-temperature gas dominates the inflowing gas mass on halo scales (≳20 kpc), with radiative losses offset by compression heating; (ii) this hot accretion proceeds until angular momentum support slows inward motion, at which point the gas cools to 10^4 K ; (iii) prior to cooling, the accreting gas develops an angular momentum distribution that is aligned with the galaxy disc, and while cooling transitions from a quasi-spherical spatial configuration to a more-flattened, disc-like configuration. We show that the existence of this 'rotating cooling flow' accretion mode is strongly correlated with the fraction of stars forming in a thin disc, using a sample of 17 z ∼ 0 galaxies spanning a halo mass range of 10 10.5 M⊙ ≲ M h ≲ 10 12 M⊙ and stellar mass range of 10 8 M⊙ ≲ M ⋆ ≲ 10 11 M⊙ . Notably, galaxies with a thick disc or irregular morphology do not undergo significant angular momentum alignment of gas prior to accretion and show no correspondence between halo gas cooling and flattening. Our results suggest that rotating cooling flows (or, more generally, rotating subsonic flows) that become coherent and angular momentum-supported prior to accretion on to the galaxy are likely a necessary condition for the formation of thin, star-forming disc galaxies in a ΛCDM universe.